Official Development Assistance and Educational Infrastruture in Ogun State, Nigeria - Sosanya, Oluwabukunmi Adewunmi; Nwogwugwu, Ngozi (NIU Journal of Humanities, 2023)
Official Development Assistance ( ODA) is a requirement for economic development that wealthier countries impose on less developed nations. Despite the flow of ODA to developing nations and the development assistance/aids provided to African countries for many years, there have been no appreciable improvements to their futures. Instead, the flows should originate from governmental organizations and go to the governments of developing countries. The majority of these nations still show modest rates of development. The literature on aid effectiveness is still debatable despite decades of empirical research on the link between help and growth and a significant flow of development assistance to developing countries. The study investigated the connection between ODA and the Ogun State educational system. The study adopted survey research design. The population of the study was 1,027. The sample of 288 was determined using Taro Yamane. Instrument for data collection was validated questionnaire. Respondents selected from three local governments in Ogun State, Nigeria, (Abeokuta South, Yewa South, and Ijebu Ode).  Data were analysed using descriptive and inferential statistics. The study found that, Ogun State does not receive enough official development aid to meet its needs for educational infrastructure, and there are a number of obstacles that prevent ODA from being implemented effectively in the state's educational system. The development of the educational infrastructure in the state of Ogun State depends on the efficient application of official development aid in the educational sector. A significant amount of foreign aid is given to the educational sector in Ogun State through grants and loans, employing shared information, technical help, and experience. The study concluded that Ogun State's educational sector receives direct government development aid that is carefully monitored. The official development aid provided to Ogun State's educational sector is generally goal- and project-driven, with adequate updates on the state's numerous educational infrastructure projects. The study recommended that Ogun State government should take the required actions to guarantee that official development support is appropriately utilized in the state's educational sector. Keywords: Official Development Assistance, educational infrastructure, implementation.